media aritmetică a numerelor 3-✓2 si 3+✓2 este​

Răspuns :

Răspuns:

Explicație pas cu pas:

Ma=(3-√2+3+√2):2=(3+3):2=6:2=3

Răspuns:

[tex]ma = \frac{a + b}{2} \\ \\ ma = \frac{3 - \sqrt{2} + 3 + \sqrt{2} }{2} \\ (3 - \sqrt{2} ) {}^{2} = 9 -2 \times 3 \sqrt{2} + (\sqrt{2} ) {}^{2} = 9 - 6 \sqrt{2} + 2 = 11 - 6 \sqrt{2} \\ \\ (3 + \sqrt{2} ) {}^{2} = 3 {}^{2} + 2 \times 3 \sqrt{2} + (\sqrt{2} ) {}^{2} = 9 + 6 \sqrt{2} + 2 = 11 + 6 \sqrt{2} \\ \\ ma = \frac{11 - 6 \sqrt{2} + 11 + 6 \sqrt{2} }{2} = \frac{11 + 11}{2} = \frac{22}{2} = 11[/tex]